2007
DOI: 10.1007/s10695-007-9168-z
|View full text |Cite
|
Sign up to set email alerts
|

Fish genetics and conservation research in India: status and perspectives

Abstract: Recent years have witnessed a rise in sensitivity towards protection of natural genetic resources and the environment at the international level. This is evident from the implementation of the convention on biodiversity (CBD). To conserve and optimize utilization of its bioresources, India enacted the Biological Diversity Act 2002. The conservation and management of aquatic resources is important for sustainable utilization of fisheries potential for the economic advancement of farmers and fishery workers, tod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
(29 reference statements)
0
17
0
1
Order By: Relevance
“…The exploitation rates ( E ) of RLTBs in three rivers (Chalakudy, Periyar, and Valapattanam) are higher than 0.5, indicating overfishing, whereas the exploitation level in the Periyar River almost equals the predicted E max , indicating that local populations are under extremely high fishing pressure and are vulnerable to collapse, unless management plans are implemented urgently. Genetic bottlenecks detected for the RLTBs in the rivers Valapatanam and Chalakudy (Lakra, Mohindra, & Lal, ) could therefore be attributed to high fishing pressure and exploitation rates. In all but one river, (Periyar), the lengths at first capture ( L c ) of the RLTBs were less than their mean sizes at first maturity, suggesting the possible occurrence of growth overfishing.…”
Section: Discussionmentioning
confidence: 99%
“…The exploitation rates ( E ) of RLTBs in three rivers (Chalakudy, Periyar, and Valapattanam) are higher than 0.5, indicating overfishing, whereas the exploitation level in the Periyar River almost equals the predicted E max , indicating that local populations are under extremely high fishing pressure and are vulnerable to collapse, unless management plans are implemented urgently. Genetic bottlenecks detected for the RLTBs in the rivers Valapatanam and Chalakudy (Lakra, Mohindra, & Lal, ) could therefore be attributed to high fishing pressure and exploitation rates. In all but one river, (Periyar), the lengths at first capture ( L c ) of the RLTBs were less than their mean sizes at first maturity, suggesting the possible occurrence of growth overfishing.…”
Section: Discussionmentioning
confidence: 99%
“…Species-specific sperm cryopreservation protocols have been developed for 14 species at NBFGR, Lucknow, India. The technique has been tested for 12 species through the production of progeny using cryopreserved sperm [28]. Cryopreservation of fish sperm is relatively common in the breeding and management of fish species, including salmonid, cyprinids, silurids, sturgeons [29][30][31][32].The creation of a cryopreserved sperm bank is an effective strategy for protecting the biodiversity of fish population and provides the opportunity to preserve the sperm samples of the most valuable males, which can be used in reproductive technologies in hatchery conditions.…”
Section: Sperm Preservationmentioning
confidence: 99%
“…Catches from several traditional collection centers increased during the years -2007. Since then, studies based on abundance, catch per unit effort, local knowledge and genetics have all concluded that the RLTBs have been severely overfished and become rare at traditional collection sites (Kurup and Radhakrishnan, 2006;Lakra et al, 2007;Raghavan et al, 2009). …”
Section: Collection and Export Of Rltbsmentioning
confidence: 99%